Ensuring the Education Quality by the Example of Regulationon Student Survey on Teaching Quality and Effectiveness of International Scientific Educational Center of NAS RA - Vardanyan, Narine; Ghalamdaryan, Anzhela (ՀՀ ԳԱԱ)
Higher education quality issues continue to be the focus of education experts, researchers, and policymakers in this context. The issue of involvement in the process of education quality assurance is also important, moreover, we are talking about both "internal" and "external" stakeholders. Stakeholders’ involvement is important in the sense that decisions are based on their opinions, and the education quality is continuously improved by identifying their needs, assessing their satisfaction, and studying their views on various issues. Բարձրագույն կրթության որակի հիմնահարցրերը շարունակում են մնալ կրթության ոլորտի փորձագետների, հետազոտողների և քաղաքականություն մշակողների ուշադրության կենտրոնում։ Կրթության որակի ապահովման գործընթացում ներգրավվածությունը շատ կարևոր է, ընդ որում՝ խոսքը և՛ ներքին, և՛ արտաքին շահակցիների մասին է։ Շահակիցների ներգրավումը կարևոր է հատկապես այն առումով, որ որոշումները կայացվում են նրանց կարծիքների հիման վրա, և կրթության որակի ապահովումը շարունակաբար բարելավվում է բացահայտելով վերջիններիս կարիքները, չափելով գոհունակությունը և ուսումնասիրելով նրանց կարծիքները տաբեր հարցերի շուրջ։ Роль и функции образования приобретают все большее значение и в этом контексте вопросы высшего образования продолжают оставаться в центре внимания экспертов в области образования, исследователей и политиков. В данном контексте также важен вопрос вовлеченности стейкхолдеров в процесс обеспечения качества образования, причем речь идет как о «внутренних», так и о «внешних» стейкхолдерах. Участие заинтересованных сторон важно в том смысле, что решения принимаются на основе их мнений, а качество образования постоянно улучшается за счет выявления их потребностей, оценки их удовлетворенности и изучения их мнений по различным вопросам.
Keywords: Social and Humanitarian Sciences